The In-Depth Evaluation of Suspected Mitochondrial Disease: The Mitochondrial Medicine Society's Committee on Diagnosis - Haas, Richard H. (2008)
Mitochondrial disease confirmation and establishment of a specific molecular diagnosis requires extensive clinical and laboratory evaluation. Dual genome origins of mitochondrial disease, multi-organ system manifestations, and an ever increasing spectrum of recognized phenotypes represent the main diagnostic challenges. To overcome these obstacles, compiling information from a variety of diagnostic laboratory modalities can often provide sufficient evidence to establish an etiology. These include blood and tissue histochemical and analyte measurements, neuroimaging, provocative testing, enzymatic assays of tissue samples and cultured cells, as well as DNA analysis. As interpretation of results from these multifaceted investigations can become quite complex, the Diagnostic Committee of the Mitochondrial Medicine Society developed this review to provide an overview of currently available and emerging methodologies for the diagnosis of primary mitochondrial disease, primarily focusing on disorders characterized by impairment of oxidative phosphorylation. The aim of this work is to facilitate the diagnosis of mitochondrial disease by geneticists, neurologists, and other metabolic specialists who face the challenge of evaluating patients of all ages with suspected mitochondrial disease.